Long-term stabilization of organic solar cells using UV absorbers. (23rd February 2016) - Turkovic, Vida; Engmann, Sebastian; Tsierkezos, Nikos; Hoppe, Harald; Madsen, Morten; Rubahn, Horst-Günter; Ritter, Uwe; Gobsch, Gerhard
Abstract: We are reporting on the successful implementation of UV absorbers for the long-term stabilization of organic photovoltaic devices (OPV). A set of six commercially available representatives of main UV absorber classes, commonly used for insulating plastics, were ternary-blended into the active layer, and the OPV performances were recorded under International Summit on OPV Stability standards (ISOS-3) degradation conditions. An improvement in the long-term performance of the OPV devices, manifested in the accumulated power generation (APG) increase for over a factor of 3, was found for 2-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)-5-[(hexyl)oxy]-phenol. This improvement is governed by a significantly decreased PCE loss during the burn-in period. Fourier transform infrared spectroscopy (FTIR) spectroscopy, used to trace chemical degradation over time, indicates that the stabilization of the active layer occurs due to a reduced formation of radicals facilitated by the UV screening properties of the additive.